Partial migration in a subtropical wading bird in the southeastern United States. Issue 2 (1st March 2020) - Picardi, Simona; Frederick, Peter C.; Borkhataria, Rena R.; Basille, Mathieu
Abstract: The function of migration is to allow exploitation of resources whose availability is heterogeneous in space and time. Much effort has been historically directed to studying migration as a response to seasonal, predictable fluctuations in resource availability in temperate species. A deeper understanding of how different migration patterns emerge in response to different patterns of resource variation requires describing migration patterns of species inhabiting less predictable environments, especially in tropical and subtropical areas. We provide the first individual‐based, quantitative description of migratory patterns in a subtropical wading bird in the southeastern United States, the wood stork ( Mycteria americana ). Using GPS tracking data for 64 individuals tracked between 2004 and 2017, we classified migratory behavior at the individual‐year level using information theory‐based model selection on nonlinear models of net squared displacement. We found that the wood stork population is partially migratory, with 59% of individuals seasonally commuting between winter ranges in Florida and summer ranges elsewhere in the population range (migrants), and 28% remaining in a single area in Florida year‐round (residents). Additionally, 13% of storks act as facultative migrants, migrating in some years but not in others. Comparing the distribution of residents and migrants suggests that different migratory strategies might be associated with the use of different or differently distributed resources, possibly including food supplementation from human activities. The existence of facultative migrants shows the potential for plastic change in migratory patterns. Partial migration in wood storks may be an adaptation to high heterogeneity and unpredictability of food resources. We suggest that future research should focus on wading birds as model species for the study of partial migration as an adaptation to heterogeneous and unpredictable environments.